Australian National Antarctic Research Expedition, 1948–50 - Law, Phillip G. (Polar Record, 1951)
In a recent issue of the Polar Record an account was given of the establishment by the Australian National Antarctic Research Expedition of research stations at Heard Island and Macquarie Island. These stations have now been in continuous operation for nearly three years, and the purpose of the following account is to summarize the progress made during this period.